The Effect of Pumpkin Flour and Chicken Liver Flour Substitution and Egg Concentration on the Physicochemical and Organoleptic Characteristics of Fettuccine Pasta - Pakerti, Andia Hayuning Jagadnira Bentang; Jariyah; Pratiwi, Yunita Satya (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Indonesia continues to face health problems caused by micronutrient deficiencies, which can trigger stunting. One effort to address this issue is nutritional intervention through the substitution of staple food ingredients with more nutrient-dense sources, such as fettuccini pasta made from wheat flour substituted with pumpkin flour and chicken liver. Pumpkin contains essential minerals such as Ca and Fe, while chicken liver is rich in Fe and Mg. This study aimed to produce fettuccini pasta with pumpkin flour and chicken liver substitution that meets good physicochemical and organoleptic quality. The research was conducted experimentally using a Completely Randomized Design with a factorial pattern consisting of two factors: flour proportion and egg concentration. The first factor included three levels of wheat flour:tapioca: pumpkin flour:chicken liver flour proportions (80%:10%:5%:5%, 70%:10%:10%:10%, and 60%:10%:15%:15%), while the second factor was egg concentration (10%, 15%, and 20%), each with two replications. The parameters analyzed were moisture, ash, protein, fat, carbohydrate, amylose, starch, tensile strength, water absorption, and organoleptic properties. The results showed that the best product was obtained from the treatment with flour proportion 80%:10%:5%:5% and egg concentration of 15%. This product contained 13.02% moisture, 0.99% ash, 12.13% protein, 2.25% fat, 71.62% carbohydrate, 13.94% amylose, 51.27% starch, 0.56 N/mm² tensile strength, and 48.58% water absorption. Organoleptic tests indicated scores of 3.38 for color, 3.19 for aroma, 3.03 for taste, and 3.76 for texture (all in the “slightly like” category). The best treatment also contained Fe 5.24 mg, Mg 14.4 mg, Zn 3.57 mg, and Ca 10.5 mg per 100 g. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production